Puberty phase specific growth charts: a radically new approach to the assessment of adolescent growth. (24th May 2012) - Cole, TJ; Butler, G; Short, J; Wright, CM
Abstract : Background: Current growth charts depict a child's height allowing for age and gender, but they ignore pubertal development. In adolescence height depends on pubertal development as well as age and gender, so assessment should ideally be a two-step process; first, to clinically assess puberty, and second, to assess height relative to puberty-specific centiles. Aim: To design new 4-20 year growth charts for the UK, based on the UK 1990 reference, focusing on pubertal progression as well as growth, in order to define normality. Methods: Tanner's five puberty stages were simplified into three phases of puberty – Pre-puberty (Tanner stage 1), In puberty (stages 2 and 3) and Completing puberty (stages 4 and 5). Using data for height, age and Tanner stage from the 1980 Dutch National Survey (N = 6563), Puberty Phase Specific (PPS) centile lines were estimated for each phase separately using the LMS method. Height centiles ignoring stage were also constructed with the same data, and the resulting median curve was adjusted using Cole's SITAR method to closely match the median of the UK 1990 growth reference. The same SITAR adjustments were then applied to the puberty centiles, thus recalibrating the Dutch data to match the UK 1990 reference. These PPS centiles were used to develop various chart designs for consideration by the RCPCH chart design group, along with testing in evaluation workshops. Results: The new PPS centiles demonstrate a stepwise increment of growth through puberty. Because the phases overlap widely in age, presentation on one chart is challenging, but they can be presented in a 3-page specialist Puberty Phase Specific chart used in conjunction with a new version of the existing cross-sectional UK 1990 chart. The age ranges of the phases will be presented on the cross-sectional charts as two puberty zones. These will illustrate the normal range for age at the start and end of puberty and for each puberty phase. Conclusions: This novel approach to growth chart design allows evaluation of a child's growth adjusted for phase of puberty, as well as age and gender, which should greatly improve the assessment of growth during adolescence.